The magic school bus on the ocean floor - Cole, Joanna; Degen, Bruce (New York : Scholastic, 1992)
On a special field trip aboard the magic school bus, Ms. Frizzle's class learns about the ocean and the different creatures that live there.
Wilson's Children, October 2010.
Elem. School Library Collection, October 1995.
School Library Journal starred, August 1992.
Book Links (A.L.A.), March 1996.
Library Journal Starred, September 1995.
Booklist, December 1997.
Keywords: Marine animals -- Juvenile literature; Ocean bottom -- Juvenile literature; Ocean; Marine animals; Ocean; Marine animals; Ocean bottom; Ocean; Marine animals